Up in Arms: Gun Imaginaries in Texas - Heiskanen, Benita; Butters, Albion M.; Kolehmainen, Pekka M. (Brill, 2022)
Up in Arms provides an illustrative and timely window onto the ways in which guns shape people's lives and social relations in Texas. With a long history of myth, lore, and imaginaries attached to gun carrying, the Lone Star State exemplifies how various groups of people at different historical moments make sense of gun culture in light of legislation, political agendas, and community building. Beyond gun rights, restrictions, or the actual functions of firearms, the book demonstrates how the gun question itself becomes loaded with symbolic firepower, making or breaking assumptions about identities, behavior, and belief systems. Contributors include: Benita Heiskanen, Albion M. Butters, Pekka M. Kolehmainen, Laura Hernández-Ehrisman, Lotta Kähkönen, Mila Seppälä, and Juha A. Vuori.